Analysis of properties of integral equations of the field in the aperture of an open coaxial probe - Чан, Лю; Ибраимов, И.К.; Панченко, А.Ю. (Radiotekhnika, 2019)
Acoustic sounding systems are an effective means of monitoring the lower troposphere. They find application in various fields of science and technology. The problem of developing acoustic methods and means for remote sensing of the lower atmosphere remains relevant given the importance of information on the state of the atmospheric boundary layer for the functioning of areas such as meteorology, ecology, transport, especially aviation, agriculture and others. This problem has both theoretical and technical aspects. These, for example, include solving inverse problems of sound propagation in a turbulent atmosphere, compensation for wind shear, and others. A number of companies and universities create acoustic locators – sodars and radio-acoustic sounding systems. The paper discusses their application for assessing the propagation conditions of radio waves on surface paths near the land-sea boundary. Despite the development of satellite systems for transmitting information and positioning, traditional means of communication and navigation are still in demand. They occupy their niche in the general nomenclature of radio equipment, while remaining indispensable in emergency warning systems, navigation in limited areas, in emergency situations. The effectiveness of these tools largely depends on operational information on the state of the propagation paths of radio waves. One of the most complex objects for assessing the propagation conditions of radio waves is the atmospheric boundary layer. Its condition is largely determined by the state of the underlying surface, which in turn depends on the time of day, season, rainfall and other factors. To date, only very limited theoretical models of dynamics have been created for some states of the atmospheric boundary layer despite the considerable efforts of meteorological specialists. Therefore, information is required on the spatial distribution of meteorological parameters. The most promising solution to this problem is the use of remote non-contact sensing methods based on one or another form of wave processes. Acoustic waves are significantly more sensitive to changes in air parameters than other types of radiation. The objectives of this work are to present a comprehensive methodology for using remote, non-contact sensing methods, theoretical representations of the dynamics of APS and modern software for solving problems of promptly determining the conditions of RRS on surface paths and assessing the most promising ways of developing methods and means for obtaining this information.An example of the experimental results of radio-acoustic sounding and sodar monitoring of the atmospheric boundary layer near the land-sea boundary is given. Based on these results, the spatial-temporal distribution of the index of refractive index is estimated. An analysis of the results is given. The choice of ways to develop means of acoustic sensing and processing the information received is substantiated, taking into account the progress of electronic devices and systems.